Outsourcing in the Retail Industry: From Europe to India and China - Agarwal, Sunil (2007)
Outsourcing is passing over the responsibility and accountability for performing certain business functions or activities to an outside specialized vendor that are required by a company to carry out its operation. Due to advantages of outsourcing there has been constant increase in the outsourcing activity in the European retail industry, in particular to India and China. It is becoming an important and key tool for the European retailers leaving them to concentrate more on retailing rather than other business areas. Cost reduction is always the main focus of every retailers behind outsourcing and it has been seen that number of companies have successfully implemented outsourcing and have gained their desired results.